2016
DOI: 10.1155/2016/3798729
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of the Telemonitoring Weight-Reduction Program “Active Body Control”

Abstract: The Active Body Control (ABC) weight-reduction program is based on telemonitoring of physical activity and nutrition together with telecoaching by weekly counseling letters sent by post or by e-mail. The study presented here reports the results of a 1-year follow-up of 49 patients with the metabolic syndrome who had lost weight with the aid of the ABC program in the preceding year. The weight regain after the second year in patients not receiving any further care (“ABC discontinued” group; n = 24) and the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…Dentre os estudos analisados, em relação ao tempo de duração da intervenção, o estudo com melhor resultado desenvolveu intervenções durante doze meses (Luley et al, 2014). Em relação ao tempo de duração das intervenções com obesos, é importante observar outros estudos que descreveram o acompanhamento desta população e que apresentaram redução significativa de peso nos primeiros 12 meses, mas que após 12 meses observaram ganho de peso nos participantes, considerando a perda de peso no longo prazo como modesta entre os obesos (Douketis et al, 2005;Pereira et al, 2021;Stumm et al, 2016).…”
Section: Discussionunclassified
“…Dentre os estudos analisados, em relação ao tempo de duração da intervenção, o estudo com melhor resultado desenvolveu intervenções durante doze meses (Luley et al, 2014). Em relação ao tempo de duração das intervenções com obesos, é importante observar outros estudos que descreveram o acompanhamento desta população e que apresentaram redução significativa de peso nos primeiros 12 meses, mas que após 12 meses observaram ganho de peso nos participantes, considerando a perda de peso no longo prazo como modesta entre os obesos (Douketis et al, 2005;Pereira et al, 2021;Stumm et al, 2016).…”
Section: Discussionunclassified
“…Partic-ipants were given accelerometers to investigate the efficacy of tele-monitoring physical activity and nutrition over 12 months. They showed that telemonitoring improved weight loss and markers of metabolic syndrome [37] after one year; however, during the follow-up period after the second year, significant weight regain occurred in both intervention groups [39].…”
Section: Association Of E-health Elementsmentioning
confidence: 99%
“…Eine kürzlich durchgeführte Folgestudie im vorgenannten Projekt verfolgte die ABC-Gruppe für ein weiteres Jahr (12). Um zusätzlich in Erfahrung zu bringen, ob ein Rebound-Effekt im zweiten Jahr durch eine Weiterführung der Betreuung vermieden oder gemildert werden kann, wurde die Betreuung für eine randomisierte Hälfte der Teilnehmer mit monatlichen ABC-Briefen fortgesetzt (▶ Abbildung 4).…”
Section: Langzeitbeobachtungunclassified